PENGARUH TAX PLANNING & TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN DENGAN TRANSPARANSI PERUSAHAAN SEBAGAI VARIABEL MODERASI - Faiz Anisran; Agus Futuhul Ma’wa, Muhammad (Jurnal Akuntansi Trisakti, 2023)
The purpose of this study was to examine and analyze the effect of two independent variables Tax Planning and Tax Avoidance on the value of manufacturing companies in the food and beverage sector with company transparency as a moderating variable. Secondary data processing was used in this study whose data came from IDX. The research was conducted to try to test a number of predetermined hypotheses. Specifically at IDX, 10 Manufacturing companies were observed for this study. The study period is three years (2020-2022). Panel data regression analysis is the analysis used in testing to check the validity of the hypothesis with the help of Eviews 12 software. Based on the results of this study, Tax Planning and Tax Avoidance have a positive effect on firm value. Meanwhile, company transparency has no effect or cannot strengthen the relationship between Tax Planning and Tax Avoidance variables on Firm Value.